SkinShield: A Digital Self-Management Platform for Eczema Patients in Hong Kong—A Pilot Study - Yin-Shun Chan; Lawrence K. Ma (International Journal of Health Sciences (IJHS), 2026)
Introduction: While digital tools have been documented to improve patients’ self-management of atopic dermatitis and quality of life, these technologies remain underutilized in Hong Kong, where unique environmental and dietary challenges persist. Materials and Methods: This study employed a one‑group pretest‑posttest design to evaluate SkinShield, an online platform tailored for local eczema patients, in a sample of 20 Hong Kong residents with eczema (including one caregiver). Results: Following a four‑week intervention, quantitative findings demonstrated significant improvements in eczema severity, disease‑specific quality of life, and psychological distress. Mixed repeated‑measures Analyses of Variance (ANOVA) further revealed that the platform was more effective for participants who were highly engaged during the intervention and for those with a shorter duration of eczema. Conclusions: This study provides preliminary evidence that locally tailored digital tools like the SkinShield can address the unique self‑management gaps faced by Hong Kong’s eczema population, supporting their potential integration into local dermatological care pathways.